The impact of dasatinib on pregnancy outcomes - Cortes, Jorge E. (Am J Hematol, 2015)
Prolonged survival in patients with chronic myeloid leukemia treated with BCR-ABL1-targeted tyrosine kinase inhibitors allows consideration of parenthood for patients on chronic therapy, but there are limited data about the effects of dasatinib on pregnancy. Pregnancy-related outcomes in dasatinib-treated patients or their partners reported to Bristol–Myers Squibb from clinical trials or healthcare providers through December 2013 were reviewed. Outcomes were available in 46/78 dasatinib-treated women (59%) and 33/69 partners of dasatinib-treated men (48%). Fifteen women (33%) delivered a normal infant; 18 (39%) and 8 (17%) had an elective or spontaneous abortion; and 5 (11%) had an abnormal pregnancy. There were 7 reports of fetal/infant abnormalities (encephalocele, renal tract abnormalities, and hydrops fetalis). Thirty of 33 (91%) infants fathered by dasatinib-treated men were reported normal at birth. Also, animal studies evaluated the impact of dasatinib on fertility, embryo-fetal toxicity, and development, suggesting that dasatinib may be a selective developmental toxicant. The outcomes of most pregnancies conceived by men treated with dasatinib were normal, but due to the small number of cases, further monitoring is required. Significant effects on pregnancy outcomes in women treated with dasatinib were found, supporting current recommendations that women avoid becoming pregnant during dasatinib treatment and be informed of fetal risks.